(untitled) (Castilla. Estudios de Literatura, 2020)
"Common places" extracted from the Bible in Literature have been used por centuries. This work reviwes how legends and passages fron the holy book of Christianity wre used in lurical and political productios to persuade public opinion about the events of the Mexican Revolution of 1910 and even after the assassination of the President Francisco I. Madero, in 1913, to denounce the Army’s betrayal.